Strategies and Challenges of Exclusive Breastfeeding for Career Women in Fulfilling Infant Nutrition - Fatimah, Okta Zenita Siti (International Conference on Sustainable Health Promotion, 2023)
This study aims to analyze the strategies and challenges of mothers in practicing exclusive breastfeeding and the strategies used to overcome these challenges. Using a qualitative approach, data was collected through in-depth interviews with 4 mothers who were giving exclusive breastfeeding in the Pesurungan Lor Village (main informants) and heads of companies where the mothers worked (triangulation informants). The research findings identified three main challenges, namely health factors, family support, and social challenges. Health challenges such as sore nipples or maternal health problems can affect the comfort of breastfeeding and a lack of support and understanding from family members can become an obstacle in continuing this practice. Social challenges, which include diverse societal views of the practice of exclusive breastfeeding, also affect the sustainability of this practice. The strategies identified included educational programs to increase mothers’ understanding, strong family support and workplace breastfeeding facilities. The results of this study provide in-depth insight into the complexity of the challenges and efforts that mothers make in exclusive breastfeeding, and underscore the importance of supportive strategies. The implications of this research can help the development of support programs that are more effective and focus on removing the obstacles that hinder the practice of exclusive breastfeeding for optimal fulfillment of infant nutrition.